THE USE OF TWO STAY TWO STRAY MODEL IN ENGLISH TEACHING TO INCREASE STUDENT’S LEARNING OUTCOME - Yusri, Yusri; R, Mantasiah; Jufri, Jufri (Study Program of English Literature, 2018)
The purpose of this study was to determine whether the application of cooperative learning model two stay two stray can increase student’s learning outcome in English learning. Data collection techniques used in this study consists of observation, tests and questionnaires. This study was conducted in two cycles, each cycle is carried out two meetings. In preliminary tests, the average of learning outcome in pre-test is was 53, 73, the first cycle was 65.4 and in the second cycle was 77.93. From these results it can be concluded that the use of cooperative learning model two stay two stray can increase student’s learning outcome in English learning.